IMPROVING END-TO-END ENCRYPTION SECURITY ON HTTP USING A GREGORIAN DAN JAVANESE CALENDAR-BASED KEY GENERATOR - Eko Heri Susanto; Yohanes Dwi Cahyono; Riyant Budi S (International Journal of Computer Science and Information Technology, 2025)
This research investigates an end-to-end encryption method with a dynamic key generator based on the conversion of the Gregorian calendar to the Javanese calendar to improve the security of the Hypertext Transfer Protocol (HTTP) and Hypertext Transfer Protocol Secure (HTTPS) protocols, which remain vulnerable to attacks. The research generates unique asymmetric keys down to the millisecond level without affecting the speed of the web server. However, this method has a downside: the data size (transfer size) doubles because the ciphertext encoding still uses hexadecimal